Assessment of functioning of village health nutrition and sanitation committees in a District in Maharashtra - Raviraj Uttamrao Kamble; Bishan S Garg; Abhishek V Raut; Madhukar S Bharambe (Wolters Kluwer Medknow Publications, 2018)
Background: Community participation is one of the core principles of primary healthcare. The village health nutrition and sanitation committee (VHNSC), one of the elements in implementation of the National Health Mission (NHM), is an example of community participation. There are not many studies conducted to assess the actual participation of VHNSC in health-care delivery at the village level. Objective: The objective of the study is to develop a VHNSC Maturity Index (VMI) and pilot it to assess the institutional maturity of VHNSC. Materials and Methods: This community-based, cross-sectional study was conducted in 83 villages under four Primary Health Centres (PHCs) of the Wardha Community Development block. VMI was developed, Through several discussion sessions with VHNSC members and staff of the DCM; observations of VHND; attending VHNSC monthly meetings; the VMI was finalized after piloting it in all the four PHC areas. Results: All the 83 VHNSCs were constituted as per norms led down under NHM. Forty-eight (57.8%) VHNSCs had developed an annual Village Health Action Plan, 72 (86.7%) VHNSCs had ≥4 meetings held in the past 6 months, and ≥70% attendance in the past 6 months was observed in 40 (48.2%) VHNSCs. A majority of 82 (98.8%) VHNSCs helped in organizing the village health and nutrition day, 59 (71.1%) VHNSCs monitored the implementation of national health programs. The entire untied fund received in the previous year was utilized by 68 (81.9%) VHNSCs. Conclusion: The study shows that VMI can be used for continuous monitoring and assessment tool for VHNSC to evaluate and plan different health activities.